2016
DOI: 10.1093/cz/zow006
|View full text |Cite
|
Sign up to set email alerts
|

Low-ranking female Japanese macaques make efforts for social grooming

Abstract: Grooming is essential to build social relationships in primates. Its importance is universal among animals from different ranks; however, rank-related differences in feeding patterns can lead to conflicts between feeding and grooming in low-ranking animals. Unifying the effects of dominance rank on feeding and grooming behaviors contributes to revealing the importance of grooming. Here, I tested whether the grooming behavior of low-ranking females were similar to that of high-ranking females despite difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
1
8
1
Order By: Relevance
“…On contrary, no significant influence of ranks was found in activity budgets of rhesus macaque mothers. This result contradicted with the study carried out in Japanese macaques [49]. Only significant differences were found in moving and resting between medium ranking and low-ranking mothers.…”
Section: Rank Related Differences In Activity Budgets Of Motherscontrasting
confidence: 83%
See 2 more Smart Citations
“…On contrary, no significant influence of ranks was found in activity budgets of rhesus macaque mothers. This result contradicted with the study carried out in Japanese macaques [49]. Only significant differences were found in moving and resting between medium ranking and low-ranking mothers.…”
Section: Rank Related Differences In Activity Budgets Of Motherscontrasting
confidence: 83%
“…Thus, rhesus macaque mothers of this study spent almost equal amount of time in all activities. The time allocated for different activities by different ranking mothers of the rhesus macaque contradicted with that of Japanese macaques [49] which might be the result of smaller group size. As suggested by van Schaik, et al (1983) [50], among long-tailed macaques, an increase in group size leads to less favorable time budgets, the rhesus macaques of this study were smaller in group size, which led to more favorable time budgets.…”
Section: Rank Related Differences In Activity Budgets Of Mothersmentioning
confidence: 83%
See 1 more Smart Citation
“…Several studies have shown that grooming, especially among kin and individuals of similar social rank, is reciprocal, both across individual grooming bouts and over time (Schino and Aureli, 2008). In other studies, grooming was found to be interchanged for rank-related benefits (tolerance at feeding sites: Gumert and Ho, 2008;Carne et al, 2011;Tiddi et al, 2011;Kurihara, 2016; access to infants in response to aunting behavior: Henzi and Barrett, 2002;Tiddi et al, 2010;Fruteau et al, 2011;agonistic support: Hemelrijk and Ek, 1991;Carne et al, 2011; or increased mating opportunities: Gumert, 2007;Sonnweber et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the degree to which a species is characterized by a rigid or relaxed dominance hierarchy is considered an important factor in balancing the frequency and context of cooperative interactions and competitive interactions among group members. For example, in species characterized by a strict or linear hierarchy, individuals may target grooming partners of similar social rank or attempt to groom up the hierarchy in an attempt to form alliances that enhance their social rank within the group (Xia et al, 2013;Kurihara, 2016). Within such a system, higherranking individuals typically receive more grooming than they give (e.g., mandrills, Mandrillus sphinx, Schino and Pellegrini, 2011;Tibetan macaques, M. thibetana, Xia et al, 2012, 2013.…”
Section: Introductionmentioning
confidence: 99%